Movement of woolly apple aphid (Eriosoma lanigerum) (Homoptera : Pemphigidae) on apple (Malus pumila) plant in relation to weather parameters - Bhardwaj, Sushma; Chander, R; Bhardwaj, S P (The Indian Journal of Agricultural Sciences, 2012)
A field study was carried out during 1991 and 1992 on 20-year-old 'Royal Delicious' apple (Malus pumila Mill.) trees at Mashobra, to investigate the movement of woolly apple aphid [Eriosoma lanigerum (Hausmann)]. The movement was confined to the first-instar nymphs and continued throughout the year except in severe winter at 3.8°C mean temperature (-2.5 to 9.3°C). The movement was Significantly higher (65%) from root to shoot zone than from Shoot to root zone (35%). Ambient temperature (> 10.3°C) and soil temperature (> 11. 5°C) triggered the aphid movement toward both the zones. Increase in ambient temperature from 13.2 to 26°C favoured maximum movement unless interrupted by other factors. Two simultaneous upward and downward movement peaks were recorded each year, first during mid-June and second during October-November. Rainfall> 72 rom in a fortnight affected 57% upward and 71% downward aphid movement. Subsequent rainfall resulted in 99.8-100% check in nymphal movement even in mast favourable temperature range (13.2-25.9°C). The net correlation between movement and mean maximum temperature was positive and significant, whereas it was non-sigllificant for mean minimum temperature and rainfall. Multiple regression analysis revealed 22.69 and 52.96% variation in upward and 23.74 and 47.45% in downward nymphal movement due to weather parameters in 1991 and 1992 respectively.